Impact of maternal risk factors on ethnic disparities in maternal mortality: a national population-based cohort studyResearch in context - Nicola Vousden; Kathryn Bunch; Sara Kenyon; Jennifer J. Kurinczuk; Marian Knight (Elsevier, 2024)
Summary: Background: Ethnic disparities in maternal mortality are consistently reported. This study aimed to investigate the contribution of known risk factors including age, socioeconomic status, and medical comorbidities to observed ethnic disparities in the United Kingdom (UK). Methods: A cohort of all women who died during or up to six weeks after pregnancy in the UK 2009-2019 were identified through national surveillance. No single denominator population included data on all risk factors, therefore we used logistic regression modelling to compare to 1) routine population birth and demographic data (2015-19) (routine data comparator) and 2) combined control groups of four UK Obstetric Surveillance System studies (UKOSS) control comparator)). Findings: There were 801 maternal deaths in the UK between 2009 and 2019 (White: 70%, Asian: 13%, Black: 12%, Chinese/Other: 3%, Mixed: 2%). Using the routine data comparator (n = 3,519,931 maternities) to adjust for demographics, including social deprivation, women of Black ethnicity remained at significantly increased risk of maternal death compared with women of white ethnicity (adjusted OR 2.43 (95% Confidence Interval 1.92-3.08)). The risk was greatest in women of Caribbean ethnicity (aOR 3.55 (2.30-5.48)). Among women of White ethnicity, risk of mortality increased as deprivation increased, but women of Black ethnicity had greater risk irrespective of deprivation. Using the UKOSS control comparator (n = 2210), after multiple adjustments including smoking, body mass index, and comorbidities, women of Black and Asian ethnicity remained at increased risk (aOR 3.13 (2.21-4.43) and 1.57 (1.16-2.12) respectively). Interpretation: Known risk factors do not fully explain ethnic disparities in maternal mortality. The impact of socioeconomic deprivation appears to differ between ethnic groups. Funding: This research is funded by the National Institute for Health and Care Research (NIHR) Policy Research Programme, conducted through the Policy Research Unit in Maternal and Neonatal Health and Care, PR-PRU-127-21202.